Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858367
|View full text |Cite
|
Sign up to set email alerts
|

'A bit like British Weather, I suppose'

Abstract: In this paper we present the design and evaluation of the Temperature Calendar -a visualization of temperature variation within a workplace over the course of the past week. This highlights deviation from organizational temperature policy, and aims to bring staff "into the loop" of understanding and managing heating, and so reduce energy waste. The display was deployed for three weeks in five public libraries. Analysis of interaction logs, questionnaires and interviews shows that staff used the displays to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Unfortunately, there appears to be very little literature investigating or evidencing how this can be achieved in practice. A handful of recent studies are notable for adopting participatory design and user-focused approaches to intervention design in the workplace [8,11,13,25]. However, these studies tend to be limited in one or more of the following areas: their investigation of the organisational context; the extent to which users are involved in the design process; and their ability to report quantitative evaluations of the intervention's impact on energy consumption (especially long-term).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there appears to be very little literature investigating or evidencing how this can be achieved in practice. A handful of recent studies are notable for adopting participatory design and user-focused approaches to intervention design in the workplace [8,11,13,25]. However, these studies tend to be limited in one or more of the following areas: their investigation of the organisational context; the extent to which users are involved in the design process; and their ability to report quantitative evaluations of the intervention's impact on energy consumption (especially long-term).…”
Section: Discussionmentioning
confidence: 99%
“…Most work in this area looks at the different design challenges surrounding materialising invisible and intangible energy resources and tailoring feedback on the consumption of these [47]. In order to achieve this, designers and researchers have visualised past and forecasted consumption data on mobiles [38,59] or insitu displays of electricity [45,58,62,67], heating [16], water [22,46], and food [15,74]. Others have also explored ambience and art [24,56], lighting [33,34], and physical materials [9,36,68] as feedback techniques.…”
Section: Shifting As a Sustainability Strategymentioning
confidence: 99%
“…Some through the design of eco-forecasts [37,49,54,58,62], while others have engaged with designing interactions that are directed towards specific energy consuming appliances, e.g. washing machines [8,17], electrical vehicles [7,10], and heating appliances [14,16,31].…”
Section: Scripting Towards Sustainabilitymentioning
confidence: 99%
“…Designs for both informing and assisting householders and workplaces to conserve heat have also been studied within sustainable HCI. An example of informing users to conserve heat through design is Constanza et al's [16] three-week workplace study of regulating heating by giving feedback on temperatures rather than the actual energy consumption. Their results showed that information visualizations can get people engaged with existing heating patterns through reflection.…”
Section: Informing and Assisting Householders To Conserve Heatmentioning
confidence: 99%
“…Firstly, little attention has been placed on how people use and experience these technologies in residential and everyday life [31,52,68]. Secondly, only a few user studies [10,14,16] report on how shifting, and in particular assisted shifting, is experienced in a real-life setting long-term. Hence, as a community we need more insights into how households experience smart grid technology assisting them to shift consumption in real-life settings, so we are better equipped to shape the interaction design for these scenarios in the future [62].…”
Section: Introductionmentioning
confidence: 99%